2021
DOI: 10.3390/ijerph18042153
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Associated Factors in Young Workers

Abstract: Background: This study aimed to identify the factors associated with the quality of life of young workers of a Social Work of Industry Unit. Methods: This was a cross-sectional study conducted on 1270 workers. Data were collected using a digital questionnaire built on the KoBoToolbox platform that included the EUROHIS-QOL eight-item index to assess quality of life. Demographic, socioeconomic, behavioral, and clinical variables were considered explanatory. The associations were analyzed using the ordinal logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Jurji et al (2018) investigated the participation patterns of youth in physical and sporting activity in Kuala Lumpur so that the government or local authorities can take action for the physical and mental health of youths. Louzado et al (2021) identified the factors related to the quality of life of young workers in Northeast Brazil. Matt et al (2020) explored the measures for young talent attractiveness in urban factories.…”
Section: Introductionmentioning
confidence: 99%
“…Jurji et al (2018) investigated the participation patterns of youth in physical and sporting activity in Kuala Lumpur so that the government or local authorities can take action for the physical and mental health of youths. Louzado et al (2021) identified the factors related to the quality of life of young workers in Northeast Brazil. Matt et al (2020) explored the measures for young talent attractiveness in urban factories.…”
Section: Introductionmentioning
confidence: 99%